Variants of Rhetorical Ventriloquism sermocinatio, ethopoeia, prosopopoeia (and Affine Terms) in the Rhetorica ad Herennium, Cicero, Dionysius of Halicarnassus, Quintilian, Augustine - Including Tentative Remarks on the Oratorico-Dramatic Concepts of ethos and persona, as well as Their Potential with Respect to Authorial Selfcraft in Shakespeare and Cervantes - Mayfield, DS (De Gruyter, 2018)
This book-length study is concerned with the various - vicarious and delegative - devices pertaining to rhetorical ventriloquism (sermocinatio, ethopoeia, prosopopoeia, etc.) - including their technical, conceptual, and applicative history in European and Western literatures, from Ancient to (Early) Modern times. It is published as an Online Supplement (.pdf) to (the article "Rhetorical Ventriloquism in Application", forming part of) the following DramaNet volume: History and Drama. The Pan-European Tradition. Eds. Joachim Küpper, Jan Mosch, Elena Penskaya. Berlin: de Gruyter, 2019.